Sue Kenny, Jim Ife and Peter Westoby (2021) Populism, Democracy and Community Development (Concept: The Journal of Contemporary Community Education Practice Theory, 2021)
AbstractThe book explores the relationship between the current growth in populism, the crisis within liberal democracy, and the implications of this for communities and the practice of community development. After an introductory overview the book is comprised of 14 individually authored chapters. The chapters are presented in 2 parts: Part 1 offers a framing of the macro issues; Part 2 explores populism and community development in different contexts.